How Can ChatGPT Empower Indonesian Classrooms? - Maspul, Kurniawan; Chemistry, Valerie; Melinda, Yona; Wisudayanti, Karila; Fedora; Rochmah, Dwi Febriana (Indonesian Journal Publisher, 2025)
The integration of generative AI like ChatGPT into Indonesia’s international education ecosystem presents a transformative yet contentious frontier, poised to redefine pedagogical paradigms while amplifying systemic inequities. This study interrogates ChatGPT’s dual role as a catalyst for cognitive empowerment and a potential vector of exclusion in a nation fractured by urban-rural divides, linguistic diversity, and infrastructural deficits. Through a qualitative, multi-site exploratory design spanning five Indonesian international schools, the research triangulates classroom observations, educator focus groups, and policy analyses to uncover four critical themes: Pedagogical Reconfiguration, Ethical Tensions, Cultural Negotiation, and Infrastructural Inequity. Findings reveal ChatGPT’s capacity to democratize access to personalized, constructivist-aligned learning—evidenced by a 28% improvement in student narrative coherence—while exposing stark disparities: 40% of rural schools lack adequate connectivity, and Western-centric AI models often erode local cultural identity. The study positions Indonesia’s grassroots innovations—such as hybrid AI labs and Socratic dialogue simulations—as pioneering yet precarious, demanding urgent alignment with Pancasila values and UNESCO’s equity mandates. Strategic recommendations advocate for a trifecta of training (cultivating AI-literate educators), infrastructure (mobile-first, multilingual tools), and policy (rights-based frameworks harmonized with ASEAN AI governance). Crucially, the research underscores that ChatGPT’s ethical integration hinges on localized language models, community-driven tech hubs, and cross-sector collaboration to bridge Java-centric privilege with Papua’s marginalization. As Indonesia navigates this AI-inflected crossroads, the study issues a clarion call: Without systemic investment in digital justice and cultural intelligence, generative AI risks entrenching hierarchies it promises to dismantle, rendering equitable human flourishing not an aspiration but an algorithmically mediated paradox.